Collaborative Musical Creativity: How Ensembles Coordinate Spontaneity - Bishop, Laura (Frontiers in Psychology, 2018)
Music performance is inherently social. Most music is performed in groups, and even soloists are subject to influence from a (real or imagined) audience. It is also inherently creative. Performers are called upon to interpret notated music, improvise new musical material, adapt to unexpected playing conditions, and accommodate technical errors. The focus of this paper is how creativity is distributed across members of a music ensemble as they perform these tasks. Some aspects of ensemble performance have been investigated extensively in recent years as part of the broader literature on joint action (e.g., the processes underlying sensorimotor synchronization). Much of this research has been done under highly controlled conditions, using tasks that generate reliable results, but capture only a small part of ensemble performance as it occurs naturalistically. Still missing from this literature is an explanation of how ensemble musicians perform in conditions that require creative interpretation, improvisation, and/or adaptation: how do they coordinate the production of something new? Current theories of creativity endorse the idea that dynamic interaction between individuals, their actions, and their social and material environments underlies creative performance. This framework is much in line with the embodied music cognition paradigm and the dynamical systems perspective on ensemble coordination. This review begins by situating the concept of collaborative musical creativity in the context of embodiment. Progress that has been made toward identifying the mechanisms that underlie collaborative creativity in music performance is then assessed. The focus is on the possible role of musical imagination in facilitating performer flexibility, and on the forms of communication that are likely to support the coordination of creative musical output. Next, emergence and group flow–constructs that seem to characterize ensemble performance at its peak–are considered, and some of the conditions that may encourage periods of emergence or flow are identified. Finally, it is argued that further research is needed to (1) demystify the constructs of emergence and group flow, clarifying their effects on performer experience and listener response, (2) determine how constrained musical imagination is by perceptual experience and understand people's capacity to depart from familiar frameworks and imagine new sounds and sound structures, and (3) assess the technological developments that are supposed to facilitate or enhance musical creativity, and determine what effect they have on the processes underlying creative collaboration.